Sistem Pendukung Keputusan Pembelian Sepeda Motor Menggunakan Metode Promethee - Noviyanti Sagala; Junita Junita; Cynthia Hayat (Computer Engineering Departement, Universitas Komputer Indonesia, 2020)
Motorcycle is one of the most popular vehicles by the people of Indonesia. Manufacturers continue to offer motorcycles with a variety of advantages ranging from storange capacity, type of design and other superior features due to the large number of enthusiasts and requests from the consumer. Product innovations launched by the manufacturer make it difficult for consumers to determine the motorcycle to be purchased. Each consumer has different preferences in choosing a vehicle, such as features, models or designs, price and storage. The research is focused on building a decision support system for the selection of automatic motorcyle. The Promethee method is outranking method that is applied to provide ranking results from the available alternatives according to the best preferences. The results showed that the built decision support system using Promethee can help make it easier to determine the type of automatic motorcycle that is accordance with the consumer preferences